The relationship between inflammation and remodeling in childhood asthma: A systematic review (2018)
Objectives We aimed to perform a systematic review of all studies with direct measurements of both airway inflammation and remodeling in the subgroup of children with repeated wheezing and/or persistent asthma severe enough to warrant bronchoscopy, to address whether airway inflammation precedes remodeling or is a parallel process, and also to assess the impact of remodeling on lung function. Methods Four databases were searched up to June 2017. Two independent reviewers screened the literature and extracted relevant data. Results We found 526 references, and 39 studies (2390 children under 18 years old) were included. Airway inflammation (eosinophilic/neutrophilic) and remodeling were not present in wheezers at a mean age of 12 months, but in older pre‐school children (mean 2.5 years), remodeling (mainly increased reticular basement membrane [RBM] thickness and increased area of airway smooth muscle) and also airway eosinophilia was reported. This was worse in school‐age children. RBM thickness was similar in atopic and non‐atopic preschool wheezers. Airway remodeling was correlated with lung function in seven studies, with FeNO in three, and with HRCT‐scan in one. Eosinophilic inflammation was not seen in patients without remodeling. There were no invasive longitudinal or intervention studies. Conclusion The relationship between inflammation and remodeling in children cannot be determined. Failure to demonstrate eosinophilic inflammation in the absence of remodeling is contrary to the hypothesis that inflammation causes these changes. We need reliable, non‐invasive markers of remodeling in particular if this is to be addressed.